Early developmental electroencephalography abnormalities, neonatal seizures, and induced spasms in a mouse model of tuberous sclerosis complex. (10th April 2020) - Rensing, Nicholas; Johnson, Kevin J.; Foutz, Thomas J.; Friedman, Joseph L.; Galindo, Rafael; Wong, Michael
Abstract: Objective: Tuberous sclerosis complex (TSC) is one of the most common genetic causes of epilepsy. Seizures in TSC typically first present in infancy or early childhood, including focal seizures and infantile spasms. Infantile spasms in TSC are particularly characteristic in its strong responsiveness to vigabatrin. Although a number of mouse models of epilepsy in TSC have been described, there are very limited electroencephalographic (EEG) or seizure data during the preweanling neonatal and infantile‐equivalent mouse periods. Tsc1 GFAP CKO mice are a well‐characterized mouse model of epilepsy in TSC, but whether these mice have seizures during early development has not been documented. The objective of this study was to determine whether preweanling Tsc1 GFAP CKO mice have developmental EEG abnormalities or seizures, including spasms. Methods: Longitudinal video‐EEG and electromyographic recordings were performed serially on Tsc1 GFAP CKO and control mice from postnatal days 9‐21 and analyzed for EEG background abnormalities, sleep‐wake vigilance states, and spontaneous seizures. Spasms were also induced with varying doses of N‐methyl‐D‐aspartate (NMDA). Results: The interictal EEG of Tsc1 GFAP CKO mice had excessive discontinuity and slowing, suggesting a delayed developmental progression compared with control mice. Tsc1 GFAP CKO mice also had increased vigilance state transitions and fragmentation. Tsc1 GFAP CKO mice had spontaneous focal seizures in the early neonatal period and a reduced threshold for NMDA‐induced spasms, but no spontaneous spasms were observed. Significance: Neonatal Tsc1 GFAP CKO mice recapitulate early developmental aspects of EEG abnormalities, focal seizures, and an increased propensity for spasms. This mouse model may be useful for early mechanistic and therapeutic studies of epileptogenesis in TSC.